Genome‐wide scan for runs of homozygosity in the composite Montana Tropical® beef cattle. (8th August 2019) - Peripolli, Elisa; Stafuzza, Nedenia Bonvino; Amorim, Sabrina Thaise; de Lemos, Marcos Vinícius Antunes; Grigoletto, Laís; Kluska, Sabrina; Ferraz, José Bento Sterman; Eler, Joanir Pereira; Mattos, Elisângela Chicaroni; Baldi, Fernando
Abstract: The aim of this study was to assess the distribution of runs of homozygosity (ROH) and autozygosity islands in the composite Montana Tropical ® beef cattle to explore hotspot regions which could better characterize the different biological types within the composite breed. Montana animals ( n = 1, 436) were genotyped with the GGP‐LD BeadChip ( 30, 000 markers). ROH was identified in every individual using the plink v1.90 software. Medium and long ROH prevailed in the genome, which accounted for approximately 74% of all ROH detected. On an average, 2.0% of the genome was within ROH, agreeing with the pedigree‐based inbreeding coefficient. The Montana cattle with a higher proportion of productive breed types showed the highest number of autozygosity islands ( n = 17), followed by those with a higher proportion of breeds adapted to tropical environments ( n = 15). Enriched terms ( p < .05) associated with the immune and inflammatory response, homeostasis, reproduction, mineral absorption, and lipid metabolism were described within the autozygosity islands. In this regard, over‐represented GO terms and KEGG pathways described in this population may play a key role in providing information to explore the genetic and biological mechanisms together with the genomic regions underlying each biological type that favoured their optimal performance ability in tropical and subtropical regions.